Review on Control Arm of Vehicle (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Front control lower arm are used in suspension system of vehicles. The current researchreviews the existing work conducted in improving design of lower control arm. These researches areconducted using both experimental and numerical techniques. The studies explore different techniques,including finite element analysis (FEA), topology optimization, and evolutionary structural optimization(ESO), to enhance the performance, durability, and cost-effectiveness of front control lower arm. The useof computational methods, such as FEA and CAD software, enables researchers to analyze and modelthe behavior of these components under various loading conditions and optimize their designparameters. The studies emphasize the importance of considering factors such as material selection,weight reduction, fatigue life, and structural efficiency in the design and optimization process.